Effect of pH on lactic acid production from acidogenic fermentation of food waste with different types of inocula. (January 2017) - Tang, Jialing; Wang, Xiaochang C.; Hu, Yisong; Zhang, Yongmei; Li, Yuyou
Highlights: LA was produced from food waste using three inocula. The highest LA yield was obtained at pH 5 using fresh food waste as the inoculum. LA was observed to degrade to VFAs at pH 6. VFA compositions varied significantly with different inocula supplied. Lactobacillus could be enriched (83.4–98.5%) during the fermentation process. Abstract: Effect of acidic pH (4, 5, 6 and uncontrolled) on lactic acid (LA) fermentation from food waste was investigated by batch fermentation experiments using methanogenic sludge, fresh food waste and anaerobic activated sludge as inocula. Results showed that due to the increase of hydrolysis, substrate degradation rate and enzyme activity, the optimal LA concentration and yield were obtained at pH 5, regardless of the inoculum used. The highest LA concentration (28.4 g/L) and yield (0.46 g/g-TS) were obtained with fresh food waste as inoculum. Moreover, after the substrate was completely utilized, the lactic acid bacteria population sharply decreased, and the LA produced was converted to volatile fatty acids (VFAs) at pH 6 within a short period. The VFA components varied with the inoculum supplied. Microbial community analysis using high-throughput pyrosequencing revealed that diversity decreased and a high abundance of Lactobacillus (83.4–98.5%) accumulated during fermentation with all inocula.